Creativity and Graphic Design Skills Improvement for the Content Creator Community using Logo Creation Training - Ninik Agustin; Mochamad Taufiqurrochman Abdul Aziz Zein (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
MTs Sultan Agung Kalipoh in Kebumen Regency is one of the junior high schools that established a content creator community since 2021. However, despite having computer laboratory facilities, those students primarily relied on smartphone applications indicating basic graphic design knowledge level within their community. Therefore, it is necessary to enhance their creativity and computer-based graphic design skills through learning how to design logo using CorelDraw and Photoshop in form of case study. The community service program was conducted in four (4) phases: analysis of situation, formulation of possible solutions, logo creation training, and evaluation. The results showed a notable 59% increase in logo creation experience indicating of the enhanced creativity in graphic skills. Moreover, there was an 80% improvement in knowledge regarding graphic application functions, and a 75% improvement in the ability to create logos.